THE QUALITY OF NUTMEG SEEDS AND MACE FROM NORTH SULAWESI - Roeroe, Henriette Jacoba; Marmis, Joubert; Tongkeles, Nelly Selvia; Lengkey, Lady (JURNAL LPPM BIDANG SAINS DAN TEKNOLOGI, 2015)
Nutmeg seeds and mace quality are important export commodity from North Sulawesi. Recently, Indonesian nutmeg seeds and mice were contaminated by aflatoxin which was emerged in the storage. This resulted in decrease in price and demand of nutmeg especially from European countries. Aflatoksin scientifically proven can cause cancer. Thus, the products should follow the quality control test to insure the safety and health of consumers to be exported to European countries. This study aimed to know the nutmeg seeds and mace quality using descriptive statistic method. The result showed that 77 nutmeg seeds and 14 mace exports sample tested in 2010 - 2013 qualified for standard quality according to Indonesian National Standard (SNI). However, those samples were contained Aflatoxin ranged between 1.67ppb to 2.00 ppb. This indicated that SNI was no longer able to determine the quality of the nutmeg seeds and mace for export.